1982
DOI: 10.1002/anie.198207761
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of N‐Acyl‐2‐(diethoxyphosphoryl)glycine Esters and Their Use in the Synthesis of Dehydroamino Acid Esters

Abstract: previously found at room temperature""], the C3-C3' bridge bond length (1.417 A, Fig. Id) is remarkably short. Fig. I. Electron density distribution in the bonds of 1 aqd bond lengths [A] at -155 "C. The contours are drawn at intervals of 0.05 eA-' and the standard deviation of the bond lengths is 0.001 A. The atoms are not numbered in accordance with IUPAC rules. Crystallographic data of 1 (C,H,O): for data at room temperature see [11; at -155 "C: a = 10.7598(7), b=6.8256(4), c=8.396(1)A,,!3=110.999(5)": C2/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…7). When Cbz-protected phosphonate 20 (Schmidt et al 1982, 1984; Schmidt and Wild 1985; Hamzavi et al 2003) was employed in the Wittig-Horner reaction with aldehyde 10 , Cbz-protected δ-azido-didehydro α-amino acid ester ( Z )- 21 was obtained in 81 % yield (calculated as traces of aldehyde 10 could not completely be removed). Stereoisomer ( E )- 21 could also be isolated in 3 % yield, and again, application of the established 1 H NMR criteria for the distinction of ( Z )- and ( E )-didehydro amino acids (Mazurkiewicz et al 2005) confirmed the stereochemical assignment.…”
Section: Resultsmentioning
confidence: 99%
“…7). When Cbz-protected phosphonate 20 (Schmidt et al 1982, 1984; Schmidt and Wild 1985; Hamzavi et al 2003) was employed in the Wittig-Horner reaction with aldehyde 10 , Cbz-protected δ-azido-didehydro α-amino acid ester ( Z )- 21 was obtained in 81 % yield (calculated as traces of aldehyde 10 could not completely be removed). Stereoisomer ( E )- 21 could also be isolated in 3 % yield, and again, application of the established 1 H NMR criteria for the distinction of ( Z )- and ( E )-didehydro amino acids (Mazurkiewicz et al 2005) confirmed the stereochemical assignment.…”
Section: Resultsmentioning
confidence: 99%
“…The route shown in scheme 1 is therefore, a novel synthesis of amino acids (ref. 3,4). Starting from aldehydes, protected amino acid esters having two additional carbon atoms are formed in a Homer type condensation.…”
Section: Synthesis Of Dehydroamino Acids and Amino Acids From N-acyl-mentioning
confidence: 99%
“…3,4) an effective three-step synthesis of N-acylphosphoryl glycine esters starting with hydroxyglycine (1) which is readily accessible from technical glyoxylic acid hydrate and benzylcarbaminate (ref. 5).…”
Section: Synthesis Of Dehydroamino Acids and Amino Acids From N-acyl-mentioning
confidence: 99%
“…Via the Michaelis-Arbuzov reaction with a-chloroglycinates. One of the rst synthesis procedures for the aphosphonoglycinates 47a-e was reported by Schmidt et al in 1982 and consists of a Michaelis-Arbuzov reaction involving trimethyl phosphite and chloroglycinate 45, which is more reactive than the methoxyamino ester precursor 44 (Scheme 10). 12,13 Aer the removal of the Cbz protecting group, the free amine was then transformed into a series of N-Boc, N-acetyl or N-formyl derivatives, with the dipeptides 47a-e showing good yields from 78 to 91%.…”
Section: Introductionmentioning
confidence: 99%